(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: The study aims to understand the impact of healthcare service quality on customer satisfaction at the Tripoli Medical Center in Libya, and to achieve this goal, the study adopted a descriptive-analytical quantitative methodology. The study community consists of all customers who receive service from the Tripoli Medical Center for the year 2021-2022. The sample was chosen randomly, and 550 questionnaires were distributed and 391 were returned. The results showed a statistically significant effect of the dimensions of healthcare service quality (reliability, responsiveness, tangibles, empathy, and security) on customer satisfaction at the Tripoli Medical Center. The study made several recommendations, the most important of which is the need to improve healthcare service quality by government hospitals in Libya to be more responsive to customer expectations.